EDUKASI ALUR SISTEM INFORMASI PUSKESMAS SEBAGAI UPAYA MENINGKATKAN EFISIENSI PELAYANAN KESEHATAN DI PUSKESMAS SAPTA TARUNA PEKANBARU - Yuliana, Anastasya Shinta; Khairunnisa, Khairunnisa; Andriani, Annisa; Melisa, Melisa; Fauzan Aidhil, Muhammad (Awal Bros Journal of Community Development, 2025)
A management information system is a system that is part of the internal workings of a business consisting of the use of documents, people, technology and procedures in management accounting. A management information system is also a logical system that provides all information to assist the operational, management, and decision-making functions of an organization. Management information system (SIM) is an information system that can create output results using inputs and various processes needed to achieve certain goals in a management matter. Management information system is a comprehensive system, aiming to present information that is much broader than historical accounting information. Information technology can overcome limitations to manage existing resources more quickly, efficiently and effectively. One of the management information systems in health services is the Puskesmas Information System (SIMPUS), which is a digital system designed to support integrated management of health services at Puskesmas. This system helps in the process of patient registration, recording medical history, managing drugs, and reporting to the Health Office. The purpose of this activity is to provide education and understanding of the workflow and benefits of SIMPUS implementation to health workers at Puskesmas. With this counseling, it is hoped that the efficiency and accuracy of the service will be improved.